Detailing sexual outcomes after treatment of localised prostate cancer with focal therapy using various energy sources: protocol for a mixed-methods study. Issue 12 (15th December 2020) - Fiard, Gaelle; Kelly, Daniel; Yap, Tet; Emberton, Mark
Abstract : Introduction: Focal therapy has emerged as a promising treatment option for men with localised prostate cancer. However, most of the evaluation of postoperative function has taken place at a relatively high, non-granular level. Most of the data we use to provide informed consent for our patients is obtained from retrospective series, or derived from prospective studies whose primary outcome was oncological. Finally, most studies have focused on erectile function and overlooked other, presumably important, elements of male sexual function. The present study aims at studying in-depth the sexual consequences of focal therapy with various energy sources. Methods and analysis: This will be a mixed-methods research study based on a retrospective and prospective cohort, recruited in parallel. The retrospective cohort will consist of patients treated with focal irreversible electroporation, and the prospective cohort of patients treated with three focal therapy energies. Participants will be recruited from two UK urology centres, one National Health Service and one private. On consent, patients will fill in self-administered validated questionnaires (International Index of Erectile Function-15 (IIEF-15), Male Sexual Health Questionnaire-Ejaculatory Dysfunction-Short Form (MSHQ-EjD-SF)) and semistructured interviews will be organised to collect patients' expectations and postoperative changes in domains such as erection, ejaculation, orgasm, libido/sexual desire, masculinity/virility, penile morphology, pain or discomfort, regret, shame, cancer-related stress, overall impact and partner satisfaction. An exploratory thematic analysis will be performed to detail recurring themes that will be grouped into clusters of experiences. We will then be able to find clusters of agreement and disagreement that will be illustrated using exemplar patient quotations. Ethics and dissemination: Ethical approval was obtained (Regional Ethics Committee reference 20/NW/0335), as well as Health Research Authority approval. Results will be published in open-access peer-reviewed journals. Findings will also be translated into patient information resources (leaflets, online information sheets). Trial registration number: ISRCTN11634296 ; Pre-results.